Studi Evaluasi Pembangunan Ekonomi Kabupaten Tegal Periode 2001 – 2005 - Oke Setiarso (EKO-REGIONAL, 2007)
This research is purposed to evaluation the economic development process of Tegal Regency. The economic outcomes evaluation is important to know how the success of development activities, inhabiting factors and affectivities of the economic development policy to support the economic development activities of Tegal regency during five years, 2001 to 2005. The measurement of the economic outcomes should be met two approaches,  the macro economic indicators and the regional economic indicator.Keywords: economic development, economic outcome, economic indicator